Escherichia coli and food safety - Dümen, Emek; EKİCİ, GÖZDE (IntechOpen, 2019)
Foodborne pathogens are evaluated as an important risk factor in terms of public health in developed and developing countries due to their extensiveness all around the world. Escherichia coli and other coliform bacteria are important foodborne pathogens. Some of the most important sources of contamination for these groups of microorganisms are reported as: areas with unfavorable hygiene, contaminated waste water, meat products, cereal products and vegetables. Total coliform bacteria and E. coli count is known to be the indicator of unfavorable hygienic conditions and fecal contamination in foods. Foodborne diseases, however, are a global issue. A joint approach by all countries and related international organizations is a prerequisite for detection and control of foodborne problems that pose a threat to human health and international trade. Despite their complicate biology, epidemiology and analyses, most foodborne diseases are preventable. It is of vital importance for public health that consumers and food producers act in accordance with the principles regarding internationally accepted safety methods.
Keywords: Escherichia Coli; Food Safety; Foodborne Diseases